2021
DOI: 10.1007/s13205-021-03072-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance profiling of Staphylococcus aureus isolated from traditional cheese in Yunnan, China

Abstract: The prevalence of staphylococcal infection and the emergence of multidrug resistance of Staphylococcus aureus (S. aureus) are major concerns in food safety and public health. This study aimed to investigate the prevalence of S. aureus isolated from traditional Chinese Rubing and Rushan cheese, antimicrobial resistance profiles, genomic characteristics, and predict antimicrobial resistance genes (ARGs). From 124 samples, 18 of 62 (29.03%) of Rubing and 5 of 62 (8.06%) of Rushan cheese were confirmed to be S. au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Nowadays, studies on the prevalence and characterization of S. aureus isolated from final dairy products available for consumers are very common, with examples from China, Norway, and Greece, among other countries [ 24 , 25 , 26 , 27 , 28 , 29 ]. In addition, numerous articles have been published on the prevalence and characterization of S. aureus in raw milk, especially in China, Iran, and Australia [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, studies on the prevalence and characterization of S. aureus isolated from final dairy products available for consumers are very common, with examples from China, Norway, and Greece, among other countries [ 24 , 25 , 26 , 27 , 28 , 29 ]. In addition, numerous articles have been published on the prevalence and characterization of S. aureus in raw milk, especially in China, Iran, and Australia [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported the WGS-based prediction of S. aureus AMR in food (Zhang F. et al, 2022;Fanelli et al, 2022;Li et al, 2022;Sri Prabakusuma et al, 2022;Wu et al, 2022). Resistance prediction databases, such as CARD, MEGARes, and AMRFinder, generally rely on BLASTn analysis and require significant computational resources and time (Gordon et al, 2014;Babiker et al, 2019).…”
Section: Wgs-based Surveillance Of Amr In S Aureusmentioning
confidence: 99%
“…According to the results of the molecular study, the isolates of subcluster IA2a (MP2, CR5, CE1, CMP1) showed a similarity of 62%. This subcluster was classified into two subclusters, where only one isolate (12) belonged to the subcluster 1A2a1, while the subcluster 1A2a2 consisted of 3 isolates (MP2, CR5, CE1) which belonged to the (MP2, CR5, CE1), which showed a similarity of 88%. From these isolates, only two isolates (MP2, CR5) showed a similarity of 86 %.…”
Section: Cluster Analysis Of Genotyped Food Isolatesmentioning
confidence: 99%
“…A 10 5 bacteria/gram concentration in the foods is adequate for producing the toxin and inducing of the illness (8,9) . Numerous researches showed that 15-80% of S. aureus which have been separated from a variety of the food sources (such as ice cream, dairy products and meats) (2,(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%